PAPARAN IKLAN ROKOK DAN PERILAKU MEROKOK PADA REMAJA SMP DI KABUPATEN BANTUL DAERAH ISTIMEWA YOGYAKARTA TAHUN 2011 - , Heni Trisnowati, Dra. Yayi Suryo Prabandari, M.Si, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background : The high cost of cigarette advertising in the Yogyakarta City leads to a trend of the promotion shift to the rural areas such as Bantul Regency. That age group of 13-15 years generally categorized as teenagers of junior high school age, and they are easily persuaded by advertisement. Objective : The study was aimed to determine the correlation between cigarette advertising exposure and smoking behaviour among teenagers at junior high schools in Bantul District, Yogyakarta Special Province. Methods : This study was an observational analytical research with cross sectional design used to determine the correlation between cigarette advertising exposure and smoking behaviour among teenagers at junior high schools of Bantul District. The population were all students at junior high schools in Bantul District. Total sample was 185 students from six randomly selected schools. Univariate, bivariate and multivariate analysis were performed to the questionnaire answers. Result : The number of teenagers who had tried smoking was 39.5%, current smoker was 58.9% and susceptible to smoking was 11.6%. The proportion of boys who tried smoking was higher (63.5%) compared to girls (8.6%). The analysis showed that there was a significant correlation between cigarette advertising exposure and smoking behaviour among teenagers at Junior High School in Bantul District (p = 0.00). The main factors associated with teenagers smoking behaviour was the male gender, high leves of cigarette advertising, close friends who smoke, smoking older brother, and parents who pay little attention to their children. Conclusion : Cigarette advertising exposure has a considerable influence on teenagers smoking behaviour at junior high school of Bantul District. The effective of health promotion programs need to be done to overcome the influence of cigarette advertising exposure and appropriate policies needed to restrict cigarette advertising in the vicinity of school areas.